2014
DOI: 10.1039/c4ay01519c
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up mass spectrometric sequencing of microRNA

Abstract: By using the acidity of MALDI matrix at high temperature, sequencing ladders of miRNA were generated. The accurate monoisotopic mass of each RNA fragment was measured by MALDI SpiralTOF. Analysis of nucleotide identity and complementary sequencing ladders allowed 100% sequence coverage and accuracy to be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“… 13 Acid hydrolysis can be performed directly in the MALDI matrix, circumventing the need for desalting after mass ladder generation. 21 Sequence confirmation for modified L-RNA has also been demonstrated using liquid chromatography (LC) coupled ESI-MS, making use of an end-labeling technique to generate single-ended reads free of internal fragments. 22 Nonetheless, no generalized procedure for fragmentation and de novo bidirectional sequencing of modified RNA has been presented.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Acid hydrolysis can be performed directly in the MALDI matrix, circumventing the need for desalting after mass ladder generation. 21 Sequence confirmation for modified L-RNA has also been demonstrated using liquid chromatography (LC) coupled ESI-MS, making use of an end-labeling technique to generate single-ended reads free of internal fragments. 22 Nonetheless, no generalized procedure for fragmentation and de novo bidirectional sequencing of modified RNA has been presented.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm searches for miRNA bearing queried partial sequence and matches it to known miRNA. Partial sequences of miR-153 that were obtained through mass spectrometric measurements in our laboratory [ 6 ] were queried in MicroRNA Multitool, and the results of matching number of miRNA are tabulated in Table 1 . From these results, it is clear that hsa-miR-153 (whose sequence is 5′ p UUGCAUAGUC ACAAAAGUGAUC-OH 3′) can be positively identified using the unique fragment [5′ pUUGCAUAGUC 3′], which is 45.4% of the miRNA sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of high throughput assays for the analysis of miRNA has made MS a more appealing technique for miRNA measurements. We recently demonstrated that MS can be used for the accurate detection and de novo sequencing of miRNA [ 6 ]. Nakayama et al also reported a method for the direct identification of miRNA using high resolution mass spectrometry in conjunction with database searching [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For sinapinic acid (SA) matrix solution, 20.0 mg of SA was dissolved in 1.0 mL of 50% ACN with 0.1% TFA. For 3-hydroxypicolinic acid (3-HPA) matrix solution, 35.0 mg of 3-HPA and 8.80 mg of ammonium citrate dibasic were dissolved in 1.0 mL of 10% ACN with 0.1% TFA [17]. To dissolve the powder of each matrix compound, the matrix solution was vortexed 1-2 min.…”
Section: Preparation Of Solutionsmentioning
confidence: 99%
“…For instance, 2,5-dihydroxybenzoic acid (DHB) is the preferred MALDI matrix for measuring protein molecules. Whereas, 3-hydroxypicolinic acid (3-HPA) is the MALDI matrix for oligonucleotide measurements [17]. To ensure the approach of using MAC ions as internal references is applicable when other MALDI matrices are used, the driftscopes of several commonly used MALDI matrices were acquired.…”
Section: Detection and Characterization Of Matrix Cluster (Mac) Ionsmentioning
confidence: 99%